Supersymmetric method for constructing quasi-exactly solvable potentials - Tkachuk, V.M. (Condensed Matter Physics, 1999)
We propose a new method for constructing the quasi-exactly solvable (QES) potentials with two known eigenstates using supersymmetric quantum mechanics. General expression for QES potentials with explicitly known energy levels and wave functions of both ground and excited states are obtained. Examples of new QES potentials are considered. Використовуючи суперсиметричну квантову механіку ми запропонували новий метод для генерування квазі-точно розв’язуваних (КТР) потенціалів з двома відомими станами. Отримані загальні вирази для КТР потенціалів з явно відомими енергетичними рівнями і хвильовими функціями основного і першого збудженого станів. Розглянуті приклади нових КТР потенціалів.